Stress vulnerability during adolescence - Duarte, Josiane O.; Cruz, Fábio C.; Leão, Rodrigo M.; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos Cesar [UNESP] (Wolters Kluwer, 2015)
Objective: This study investigated the physiological and somatic changes evoked by daily exposure to the same type of stressor (homotypic) or different aversive stressor stimuli (heterotypic) in adolescent and adult rats, with a focus on cardiovascular function. The long-term effects of stress exposure during adolescence were also investigated longitudinally. Methods: Male Wistar rats were exposed to repeated restraint stress (RRS, homotypic) or chronic variable stress (CVS, heterotypic). Results: Adrenal hypertrophy, thymus involution, and elevated plasma glucocorticoid were observed only in adolescent animals, whereas reduction in body weight was caused by both stress regimens in adults. CVS increased mean arterial pressure (adolescent: p = .001; adult: p = .005) and heart rate (HR; adolescent: p = .020; adult: p = .011) regardless of the age, whereas RRS increased blood pressure selectively in adults (p = .001). Rest tachycardia evoked by CVS was associated with increased cardiac sympathetic activity in adults, whereas a decreased cardiac parasympathetic activity was observed in adolescent animals. Changes in cardiovascular function and cardiac autonomic activity evoked by both CVS and RRS were followed by alterations in baroreflex activity and vascular reactivity to vasoconstrictor and vasodilator agents in adolescent adult animals. Except for the circulating glucocorticoid change, all alterations observed during adolescence were reversed in adulthood. Conclusions: These findings suggest a stress vulnerability of adolescents to somatic and neuroendocrine effects regardless of stress regimen. Our results indicated an age-stress type-specific influence in stress-evoked cardiovascular/autonomic changes. Data suggest minimal consequences in adulthood of stress during adolescence.